Інтеґрація і реґіоналізація — два вектори єдиної політики Євросоюзу - Зоткін, А. (Социология: теория, методы, маркетинг, 2009)
Two multidirectional vectors remain simultaneously valid within the domestic policy of European Union: the integration of European community in a single unit and the increasing regionalization of the EU countries-members. The author of the article comes to the conclusion, that the result of such multidirectional political processes is not the contradiction, but rather interaction of these two trends of domestic policy. The deepening of regionalization and partial loss of the autonomy by national govern ments of countries-members of EU is instrumental in the acceleration of the European community integration. The mechanisms of the parallel moved forward integration and regionalization must resolve territorial conflicts both among the “old” members of EU (so called “interdynastic” type of conflicts) and between the “old” and “new” EU members (“post-colonial” type of conflicts). In addition, the supranational authorities of the European Union can make use of the trend of regionalization as an effective mechanism of political management.